Systematic review of pre-operative exercise in colorectal cancer patients - Boereboom, C.; Doleman, Brett; Lund, Jonathan N.; Williams, John P. (Springer Verlag, 2016)
The aim of this systematic review was to evaluate the evidence for exercise interventions prior to surgery for colorectal cancer resection. The evidence for use of exercise to improve physical fitness and surgical outcomes is as yet unknown. A systematic search was performed of MEDLINE, EMBASE, CINAHL, AMED and BNI databases for studies involving pre-operative exercise in colorectal cancer patients. Eight studies were included in the review. There is evidence that pre-operative exercise improves functional fitness, and to a lesser extent objectively measurable cardio-respiratory fitness prior to colorectal cancer resection. There is no clear evidence at present that this improvement in fitness translates into reduced peri-operative risk or improved post-operative outcomes. Current studies are limited by risk of bias. This review highlights the common difficulty in transferring promising results in a research setting, into significant improvements in the clinical arena. Future research should focus on which type of exercise is most likely to maximise patient adherence and improvements in cardio-respiratory fitness. Ultimately, adequately powered, randomised controlled trials are needed to investigate whether pre-operative exercise improves post-operative morbidity and mortality.